Improving the Effectiveness of Internal Control System In Accordance with COSO Model - الدوغجي علي حسين; الخيرو ايمان مؤيد (Journal of Economics and Administrative Sciences, 2013)
The research aims to improve the effectiveness of internal control system according to a model COSO, by identifying the availability of system components according to the model and then improve the effectiveness of each component by focusing on areas for improvement in each component, as it was addressed to a model COSO and then Maamth with the environment, the current Iraqi by introducing some improvements on the form of some mechanisms of corporate governance of the Council of Directors, and senior management, the Audit Committee, Committee appointments, especially that supplies application available in the laws and legislation, the current Iraqi, taking into consideration to make some modifications to become parallel to those systems in place in the developed world (U.S., EU countries and others), especially since Iraq is a country open to the world. The most important conclusions reached by the research: 1. The requirements apply some mechanisms of corporate governance and of (the Board of Directors and senior management and Internal Audit Committee and the Committee on Appointments) are available through the provided materials, the Companies Act regarding the composition of the board members of executive and non-executives, which facilitates the formation of the Audit Committee and the Committee on Appointments, as is the formation of the Audit Committee members of the board of directors non-executive directors of the most important tools that contribute to improving the efficiency of the internal control system and its effectiveness The scope of the audit of internal change of focus on the financial aspects to include aspects of administrative, operational, and all aspects of activity and its contribution to value added per unit of confirmation through the provision of services and consulting.